2020
DOI: 10.1111/jan.14328
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the impact of health literacy on hospital readmission among older heart failure patients: A prospective cohort study

Abstract: Aims:To investigate the impact of limited health literacy on 1-year hospital readmission among both older men and women with heart failure.Design: Prospective cohort study. Methods:A total of 286 patients with heart failure (men = 144, women = 142) aged 65 years or older at baseline from two tertiary hospitals were enrolled from June-November 2017. Patients were followed up until November 2018. The Brief Health Literacy Screening Tool was used to assess baseline health literacy. One-year readmission after disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…Our study confirmed that the elderly living in urban residence and elderly males have shown higher hospitalization rate where these findings were consistent with previous research 11,17,[32][33][34][35]38 . Our results revealed that elderly women have lower odds of hospitalization than the elderly men and similar patterns of hospitalizations were also observed in other countries like-England 39 , Norway 17,40 , Italy 41 , but countries like Denmark 42 , Finnland 40 , South Korea 43 and Brazil 44 have shown higher hospitalization among older women than older men. Interestingly, our study have showed that married elderly was found to be less likely to be hospitalized than unmarried, these finding are analogous to the other previous studies 11,35,[45][46][47][48] .…”
Section: Discussionsupporting
confidence: 85%
“…Our study confirmed that the elderly living in urban residence and elderly males have shown higher hospitalization rate where these findings were consistent with previous research 11,17,[32][33][34][35]38 . Our results revealed that elderly women have lower odds of hospitalization than the elderly men and similar patterns of hospitalizations were also observed in other countries like-England 39 , Norway 17,40 , Italy 41 , but countries like Denmark 42 , Finnland 40 , South Korea 43 and Brazil 44 have shown higher hospitalization among older women than older men. Interestingly, our study have showed that married elderly was found to be less likely to be hospitalized than unmarried, these finding are analogous to the other previous studies 11,35,[45][46][47][48] .…”
Section: Discussionsupporting
confidence: 85%
“…The expression of HL as capabilities and competencies of the elderly people in the included articles additionally showed that based on the social status within a patriarchal society men were more likely to be able to access HL information and engage in HL activities (Parmar et al., 2014); that sex (gender) could not be a predictor of mental HL (Piper et al., 2018); and that while women may have higher levels of HL than men they are more susceptible to diabetes and that men with lower HL levels were more likely to have diabetes than men with higher HL levels (Quartuccio et al., 2018). Also, the included articles showed that in a predominantly female sample HL was measured by mental cognition (Serper et al., 2014); and that low HL was more common among women but low HL among women was associated with the advancement of age whereas low HL among men was associated with lower education levels (Son & Won, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Social class may also affect the application of HL (Thompson et al., 2017). In general, male and female genders have an influence on the self‐health management of the elderly people in terms of the level of pain or disease severity (Gwynn et al., 2016; Lei et al., 2014; MacLeod et al., 2017; Quartuccio et al., 2018; Son & Won, 2020; Verney et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results might depend on different factors. First, it was often unclear whether HL was assessed as part of clinical research or integrated into the patients’ clinical records ( Son & Won, 2020 ). Hence, these studies were not considered.…”
Section: Discussionmentioning
confidence: 99%